Socioeconomic and demographic disparities in the impact of digestive diseases in the middle East and North Africa (MENA) region - Omar Al Ta’ani; Yazan Al-Ajlouni; Chloe Lahoud; Sharifeh Almasaid; Yahya Alhalalmeh; Zaid Oweis; Pojsakorn Danpanichkul; Ali Baidoun; Saqr Alsakarneh; Dushyant Singh Dahiya; Basile Njei (International Journal for Equity in Health)
Abstract Introduction Digestive diseases (DD) pose a significant global health burden, with the Middle East and North Africa (MENA) region providing a unique landscape to study the impact of socioeconomic disparities on DD incidence and outcomes. This study examines the burden of DD in the MENA region, focusing on socioeconomic influences. Methods We utilized data from the Global Burden of Disease (GBD) dataset from 1990 to 2021, analyzing trends in incidence, mortality, and disability-adjusted life years (DALYs) for DD. Percentage changes and estimated annual percentage changes (EAPCs) were calculated for age-standardized rates, and correlations were assessed between disease metrics and socio-demographic indices, including the Socio-demographic Index (SDI), Human Development Index (HDI), and Gender Inequality Index (GII). Results Between 1990 and 2021, the total incidence of DD rose by 129.8%, from 19.7 million to 45.4 million cases. Age-standardized mortality and DALY rates decreased by 48.3% and 44.7%, respectively. Strong correlations were observed between age-standardized incidence rates (ASIR) and SDI (r = 0.90), HDI (r = 0.88), and GII (r = − 0.86). EAPCs for incidence, deaths, and DALYs were 0.79, -2.29, and − 1.88, respectively. Conclusion Despite a reduction in mortality and DALY rates, the persistently high incidence rates of DD in the MENA region underscores ongoing public health challenges. Socioeconomic factors strongly influence disease burden, highlighting the need for targeted interventions to address disparities and improve digestive disease outcomes across the region.